Pythagorean fuzzy VIKOR-based approach for safety risk assessment in mine industry - Gul, Muhammet; Ak, M. Fatih; Guneri, Ali Fuat (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Introduction: Underground mining is considered one of the most hazardous industries and is often associated with serious work-related fatalities; this paper addresses job-related hazards and associated risks. Method: A risk assessment approach is proposed (Pythagorean fuzzy environment) and a case study is carried out in an underground copper and zinc mine. Results: Results of the study demonstrate that hazards can be categorized into different risk levels via compromised solutions of the fuzzy approach. Conclusion: The study provides a theoretical contribution by suggesting a Pythagorean fuzzy numbers-based VlseKriterijumska Optimizacija I Kompromisno Resenje (PFVIKOR) approach. Moreover, it contributes to improving overall safety levels of underground mining by considering and advising on the potential hazards of risk management Practical applications: The proposed approach will improve the existing safety risk assessment mechanism in underground copper and zinc mining. (C) 2019 National Safety Council and Elsevier Ltd. All rights reserved.
Keywords: Occupational hazards; Risk assessment; Underground copper and zinc mine; Pythagorean fuzzy sets; VIKOR; ANALYTIC HIERARCHY PROCESS; OCCUPATIONAL-HEALTH HAZARDS; DECISION-MAKING; MANAGEMENT; CONSTRUCTION; PROJECT; MODEL; METHODOLOGIES; ENVIRONMENT; INTEGRATION; Engineering; Public, Environmental & Occupational Health; Social Sciences - Other Topics; Transportation